The in Vitro Anticoagulant Activity of Human Plasma Lipids - Cohen, J; Reed, C. F; Troup, S. B (Thrombosis and Haemostasis, 1965)
The present report describes the in vitro inhibition of prothrombin consumption by lipid extracted from normal human platelet-poor plasma. Pro-coagulant lipids and the test plasma lipids were dissolved in the same solvent and evaporated to dryness. The dried lipid mixture was emulsified in platelet-poor plasma, and the plasma clotted by recalcification. Inhibition of prothrombin consumption by plasma lipid was observed when the ratio of plasma lipid to procoagulant lipid equaled or exceeded 5:1. The inhibitory effect of plasma lipid on prothrombin consumption was not observed when procoagulant activity was provided by intact platelets or platelet granules.Human plasma lipids have been fractionated on silicic acid columns to permit identification of the plasma lipid component responsible for the inhibition of prothrombin consumption. The inhibitory activity is present in a lipid fraction which is 95% lecithin. Other plasma lipid components exhibit little or no inhibitory activity.